The Anthropological Model of Reading “Prescription for Soul and Body Against Epidemic Air” by 16th Century Priest Hieronim Powodowski - Krzysztofik, Małgorzata (Respectus Philologicus, 2013)
This article joins the newest trends of scientific studies on the anthropology of literature and the anthropology of the human body. It discusses a set of instructions written at the end of the 16th century by a clergyman, Hieronim Powodowski. His Prescription for soul and body against epidemic air tells readers how to avoid a plague. In those times, people’s reactions to infectious epidemic diseases were panic-stricken—an understandable response, as the death rate from plague could exceed 70%. In this article, I analyse the religious and cultural relation of spiritual–physical, and discuss the theological issues raised by the text (the picture of God). I describe the aspects of reality which, from the point of view of a renaissance preacher, are connected with the spiritual domain (God and the soul) and those which are physical (the body under a deadly threat). I also answer the question of how these two domains influence each other. Medical discourse and theological discourse are closely connected in Prescription…, as the text is rooted in biblical anthropology, according to which the spiritual and physical elements of a human being are in unity. Physical illness is a specific sign of the relation between these two elements. For this reason, humans could not be understood from the physical or the spiritual point of view alone. The entire meaning is revealed only in their connection and interdependence.
Keywords: Anthropology of Literature; Anthropology of the Body; Theology of Literature; Illness in Culture; Relation of the Spiritual and the Physical